Pengaruh Motivasi dan Disiplin Kerja Terhadap Kinerja Karyawan PT. Duta Alam Sumatera Kecamatan Merapi Barat Kabupaten lahat - Hasanah, Titi (MOTIVASI, 2020)
ABSTRACTPurpose - This study aims to determine the influence of motivation and work discipline on employee performance on PT. Duta Alam Sejahtera Kecamatan  Merapi  Barat Kabupaten Lahat.Design/methodology - The number of samples is 42 respondents. Data were obtained from questions by using a questionnaire consisting of closed and open questions. Respondents' answers were then analyzed by two-stage regression using SPSS (Statistical Package for Social Science) version 22.Findings - Based on the analysis that motivation and work discipline have a significant effect on employee performance with regression coefficient Y = 3,606 + 0,27X1 + 0,651X2 which means if motivation and work discipline variable is not equal to zero (0) then employee performance 3,606.In t test result obtained that motivation and discipline of each work have influence significantly to employee performance at PT. Duta Alam Sejahtera Kecamatan Merapi Barat  Lahat Kabupaten Lahat. In F test found that the variables of motivation and work discipline have a significant influence on employee performance on CV. Sinar Telekom Cluster Lahat.Keywords : Motivation, Work Discipline, and Employee Performance.